Trends in prevalence of overweight and obesity : Are portuguese adolescents still increasing weight? - Marques, Adilson (2016)
Objective To report the prevalence and trends of the BMI of Portuguese adolescents in 2002, 2006 and 2010. Methods 4138 boys and 4472 girls self-reported weight, height, physical activity, perception of health and life satisfaction. Results For adolescents aged 11–13 years, the prevalence of overweight/obesity decreased from 23.5 % in 2002 to 20.7 % in 2010, using IOTF cutoff points, and decreased from 32.4 to 28.4 % between 2002 and 2010 using WHO cutoff points. For adolescents aged 15–17 years, the prevalence increased from 13.9 to 16.8 % between 2002 and 2010 using IOTF cutoff, and increased from 14.8 % in 2002 to 18.2 % in 2010 when using WHO cutoff points. Although the prevalence decreased among younger adolescents and increased among older ones, the differences were not significant. Physical activity in the last 7 days (p\0.05), better life satisfaction (p\0.05) and perception of health (p\0.001) predicted lower body mass index z score. Conclusions Overall, there have been no significant changes in overweight and obesity prevalence in Portuguese adolescents from 2002 to 2010. However, the prevalence remains high and therefore it is important to continue surveillance.